Study on Durability Performance of Concrete Containing Laterite Aggregates - Khairunisa, Muthusamy (ISSR, 2015)
This paper addresses the durability performance of concrete containing laterite aggregate against corrosion, acid attack and carbonation. Two types of mixes were used, that is plain concrete (0% laterite aggregate) and another one, produced by integrating 20% of laterite aggregate as partial coarse aggregate replacement. The corrosion resistance test was conducted by immersing the 28 days water cured specimens in sodium chloride for 1, 7 and 15 days. The steel bars were then connected to the data logger to determine the corrosion potential of each specimen. The acid resistance of specimens were investigated by immersing it in hydrochloric acid solution and the mass of cubes were measured at every 100 hour until 1800 hour. Carbonation depth was determined by spraying phenolphthalein indicator on broken surface of prism with curing age up to 1 year. The corrosion potential of both types of concrete rose as experimental period become longer. The acid resistance results show the difference in total mass loss of laterite concrete and control specimen is less than 5%. Carbonation results of the specimens are also close to each other. Utilization of 20% laterite aggregate as partial coarse aggregate replacement influences the resistance of concrete upon corrosion effect, acid attack and carbonation.